West Germany and the Iron Curtain : environment, economy, and culture in the borderlands - Eckert, Astrid M., 1971- 1971- (Oxford University Press, 2019)
'West Germany and the Iron Curtain' takes a fresh look at the history of the Federal Republic and the German re-unification process from the spatial perspective of the West German borderlands that emerged along the volatile inter-German border after 1945. The text is the first environmental history of the Iron Curtain